Polymer – Polymer interaction at the nanoscale: An atomic force microscopy study of interaction stress. (August 2019) - Rahmat, Meysam; Hubert, Pascal
Abstract: A new method of polymer-polymer interaction characterization through atomic force microscopy (AFM) is presented. Unlike previous interaction characterization methods such as light scattering, and differential scanning colorimetry, the current method generates the interaction strength in terms of interaction stress. This method is based on previously developed stepwise discretization technique, and is demonstrated here through studying the interaction between polyethylene (PE) and three compatible polymers including high density polyethylene (HDPE), ultra-high molecular weight polyethylene (UHMWPE), and polyethylene high density grafted with glycidyl methacrylate (PE-g-GMA). The results showed that PE-g-GMA had the strongest interaction of 1.5 MPa with PE in air; whereas UHMWPE offered the weakest interaction (i.e. 1 MPa) and HDPE had the shortest interaction distance of 4.3 nm at the peak interaction. The outcome was shown to be in agreement with previously demonstrated principle of polymer-polymer interaction, demonstrating the new method as a simple but powerful option in polymer-polymer interaction studies. Highlights: A new comprehensive methodology to use AFM for polymer interaction characterization purpose is presented. As an example, interaction stress between polyethylene and three polymers including HDPE, UHMWPE and PE-g-GMA is studied. Strongest interaction and minimum separation distance between polymer pairs is obtained. These findings are proven to be in agreement with previously demonstrated polymer interaction principles.